THE ROLES OF GLASS CEILING BELIEFS AND ORGANIZATIONAL COMMITMENT ON SOCIAL LOAFING AMONG FEMALE EMPLOYEES - Ogungbamila, Adepeju; Uchenna Onuoha, Chibuzor; Emmanuel Job, Dada (African Journal of Social and Behavioural Sciences, 2026)
Perception of obstacles to career advancement and psychological attachment to the organization are employee attitudes that may influence negative discretionary work behaviour. This present study aims to examine the contributions of perceived glass ceiling and organizational commitment to workplace social loafing. Designed as a cross-sectional quantitative research, 271 female employees purposively selected from structured work organizations were surveyed. They completed a self-report paper-and-pencil questionnaire that measured validated scales of glass ceiling beliefs, organizational commitment, and social loafing. The research instrument was completed anonymously by the participants. High level of coefficient alpha that ranged from α = .78 to α = .85 was reported for the scales. Data were analyzed using bivariate correlation and hierarchical regression tests. Results showed that the correlation coefficient between glass ceiling beliefs (r = .33, p< .01), organizational commitment (r = .49, p < .01) and social loafing, respectively, is positive and significant. Hierarchical regression analysis indicated that glass ceiling beliefs significantly and positively predicted social loafing (β = .33, p < .01), accounting for 10% of the variance in social loafing. Organizational commitment is positively related to social loafing (β = .44, p < .01), and contributed 11% variance in social loafing. The study concluded that a perceived high glass ceiling is associated with increased social loafing among female employees who reported a higher level of organizational commitment.